Survey of healthcare experiences of Australian adults living with rare diseases. Issue 1 (December 2016) - Molster, Caron; Urwin, Debra; Di Pietro, Louisa; Fookes, Megan; Petrie, Dianne; van der Laan, Sharon; Dawkins, Hugh
Abstract Background Few studies have examined whether the healthcare needs of people living with rare diseases are being met. This study explores the experiences of Australian adults living with rare diseases in relation to diagnosis, information provision at the time of diagnosis, use of health and support services and involvement in research on their condition. Methods The survey respondents are self-selected from the population of Australian residents aged 18 years and over who are living with a rare disease. An online survey was implemented between July-August 2014. Purposive snowballing sampling was used. The results are reported as percentages with significant differences between sub-groups assessed using chi-squared analyses. Results Eight hundred ten responses were obtained from adults living with a rare disease. 92.1 % had a confirmed diagnosis, of which 30.0 % waited five or more years for a diagnosis, 66.2 % had seen three or more doctors to get a diagnosis and 45.9 % had received at least one incorrect diagnosis. Almost three quarters (72.1 %) received no or not enough information at the time of diagnosis. In the 12 months prior to the survey, over 80 % of respondents had used the services of a general practitioner and a medical specialist while around a third had been inpatients at a hospital or had visited an emergency department. Only 15.4 % of respondents had ever used paediatric services, 52.8 % of these had experienced problems in the transition from paediatric to adult services. Only 20.3 % knew of a patient registry for their condition and 24.8 % were informed of clinical trials. Conclusions These findings suggest that not all healthcare needs of people living with rare diseases are being met. Structural changes to Australian healthcare systems may be required to improve the integration and coordination of diagnosis and care. Health professionals may need greater awareness of rare diseases to improve the diagnostic process and support to meet the information requirements of people newly diagnosed with rare diseases. Health service use is likely higher than for the general population and further epidemiological studies are needed on the impact of rare diseases on the healthcare system.